Isolasi Bakteri Penghasil Indole Acetic Acid pada Tanaman Hortikultura di Perkebunan Prafi SP 1, Manokwari - Rina Anita Mogea; Waode Intan Cendrasari La Halim Putri; Hermawaty Abubakar (Jurnal Ilmu Pertanian Indonesia, 2022)
Horticultural plants are branches of agriculture that are associated with crop cultivation such as vegetables, fruit, various ornamental plants, and medicinal plants that require compounds to accelerate the formation of roots which can be done by using growth regulators. One of the growth regulators needed for plants is auxin or Indole Acetic Acid (IAA). The presence of bacteria that act as producers of IAA can be used to stimulate the growth of horticultural plants. Therefore, the exploration of bacteria that have the potential to produce auxin in the future can provide an important and significant role in increasing agricultural production. This study aims to isolate, select, measure the value of IAA, and characterize IAA-producing bacteria. Isolation of auxin-producing bacteria using general media of growth bacteria, i.e., Nutrient Agar (NA) and Nutrient Broth (NB). The location for sampling of rhizosphere soil was Prafi SP 1 Plantation, Manokwari, Indonesia. The results showed that as many as 9 bacterial isolates were obtained from the rhizosphere of horticultural plants. After selection of auxin-producing bacteria, 2 bacteria isolates (IBPA 3 and IBPA 5) were obtained which were able to produce IAA. IAA concentration value in IBPA 3 isolate is 42.178 ppm and in IBPA 5 isolate is 27.65 ppm. The characteristics of IBPA 3 isolate refer to the genus Bacillus and IBPA 5 isolate refer to the genus Pseudomonas. Keywords: agriculture, bacteria rhizosphere, indole acetic acid